The Winning Strategy of United Tractors - Sari Wahyuni; Monica Devina; Angelica Fadya Noventi; Akbar Chinindio; Dendy Putra Ladumei (AIBPM Publisher, 2018)
United Tractor (UT) is a company originally engaged in the distribution of construction machinery. The objective of this research is to explore the winning strategy of United Tractors. We use secondary data which is retrieved from company's official website, annual reports, and other relevant sources. Regarding the business operation, United Tractors conducted differentiation strategy and decided to take the steps to expand different market segments. Therefore, UT is vertically integrated the business operation and build relationship with other companies which have brought to the sustainability. It helps them to become a leader in the market through diversify their products and services. Eventually, UT upholds total solutions to customers and continually conducts innovation in order to stay in the lead. Keywords: differentiation strategy, innovation, market leader, sustainability, vertical integration